The Effect of Information Quality and Service Quality on Tokopedia Marketplace Consumer Satisfaction (Case Study on Students of the Faculty of Economics National University PASIM - Andri Asoka Sidantara Rosadi; Muhamad Alfani (International Journal of Integrative Sciences, 2023)
Tokopedia.com is a prominent digital buying and selling company in Indonesia, known for rapid growth since its establishment. It operates as a marketplace and online store platform, enabling individuals, small businesses, and brands to manage online stores. In 2015, Tokopedia offered free access to its core services to boost internet development in Indonesia, with a focus on supporting micro, small, and medium-sized enterprises (MSMEs). The company's research uses descriptive and associative methods to assess customer satisfaction, with a strong positive correlation between information quality and customer satisfaction. Information quality and service quality combined account for 87.4% of customer satisfaction, with the remaining 12.6% attributed to unexamined factors